Impact of Obesity on Metabolic Hormones and Interleukins in Obese Individuals with and without Metabolic Syndrome - Ahmed, Reyam E.; Al-Lami, Makarim Q. (Iraqi Journal of Science, 2026)
Obesity is a medical condition that occurs when the body mass index (BMI) is ≥ 30 kg/m2. Many factors cause obesity, such as unhealthy lifestyle, socioeconomic status, and genetic factors. Chronic low-grade inflammation is one of the hallmarks of obesity, and genetic factors also cause it. Obesity affects many different organ systems. This study aimed to investigate the impact of obesity on metabolic hormones and interleukins in obese individuals with and without metabolic syndrome (MetS). The study includes 140 Iraqi participants’ (60 males and 80 females), who were divided into 65 obese individuals with MetS, 50 obese individuals without MetS, and 25 healthy controls during their attendance at the Endocrinology and Diabetes Consultation/ Al-Imamain Al-Kadhimain Medical City / Baghdad / Iraq, from the period (January 2023 to July 2023). The average age of participants ranged from 20 to 60 years. Blood samples (5ml) were collected from all study participants by intravenous phlebotomy. Metabolic hormones (leptin, resistin, and adiponectin) and [interleukin-10 (IL-10), interleukin-13 (IL-13), and interleukin-18 (IL18)] were measured using enzyme-linked immunosorbent assay (ELISA) kits (sandwich method). The results revealed a significant (P<0.05) increase in leptin, and resistin in the obese with MetS and without MetS groups compared with the control group, and a significant decrease in adiponectin level in the obese with MetS group and without MetS groups compared with the control group. According to interleukins, there was a significant decrease in the mean value of IL-10 level in the obese with MetS group and without MetS group compared with the control group, and a significant increase in IL-13 and IL-18 levels in the obese with MetS group and without MetS group compared with the control group. In conclusion, obesity affects the levels of metabolic hormones and interleukins. Some hormones and interleukins increase while others decrease with obesity.